GAYA HYPERREALIS DENGAN SOUND EFFECT FILM FIKSI PANDORA TANARA - Ded Ded Shaputra (Cinelook: Journal of Film, Television, and New Media, 2025)
The film Pandora Tanara tells the story of a mother named Tanara who locks up her son Seren, Tanara gives drugs which cause paralysis to the child. Seren has a pen pal named Gany. The concept of sound arrangement in this film is the application of a hyperrealist style to create suspense in the story. To apply the hyperrealist style the author uses sound effects as an application of the hyperrealist style. The application of a hyperrealist style with sound effects can be enhanced using the Foley technique. The foley technique can be applied to several sound effects that sound non-dominant to become dominant or sounds that are not real become real. Thus the sound that is applied with the Foley technique will sound real like the sound of a heartbeat.